Becoming secular: Biographies of disenchantment, generational dynamics, and why they matter. (June 2022) - Burchardt, Marian
In many Western societies, support for policies concerning the secularization of the public sphere or the state often seems to be driven by secularized majority populations considered to be largely homogeneous. In this article, by contrast, I draw on the case of the Canadian province of Quebec to show that, as a fundamental element of conflicts over secularism, secularist activism emerges from particular generational dynamics, especially those of the so-called 'baby boomers'. My main argument is that while the baby boomers' collective experiences have shaped their secularist outlook, there are a variety of biographical trajectories and engagements with spirituality that the public image of this generation tends to hide. The article is based on biographical and ethnographic research carried out between 2012 and 2018.